Resource sharing and resource sparing, understanding the role of production intensity and farm practices in resource use in shrimp aquaculture. (15th June 2021) - Davis, Robert P.; Boyd, Claude E.; Davis, D. Allen
Abstract: Aquaculture production is an important part of the global food supply and has equaled or surpassed fisheries production as the main source of aquatic foods. Aquaculture is a resource intensive practice that can use large amounts of land, water, energy, and cause pollution and degradation to the local environment. Intensive production practices have been criticized in the past for causing environmental harm; however recent studies have suggested that resource use may decrease with increasing production intensities at the farm level. Here we used a conceptual farm to access the impact of a few key production parameters on land, water, and energy use. A series of calculations were conducted at various production intensities with modifications made to the type of feed used and water exchange rate. The resulting relationships were then modeled with production intensity. Additionally, the effect of various feedstuffs on embodied resource coefficients was examined through varying protein and carbohydrate feedstuffs. Land and water use were found to have an asymptotic relationship with production intensity, with the most important factor in land use being production intensity and the most important factor in water use being the water exchange rate. Energy use was found to be higher with a diet that has fish meal as a protein source and at higher water exchange rates. The most land intensive diets used for shrimp contained high fish meal with rice as carbohydrate feedstuffs (0.550 ha/tonne). The most water intensive diet was no fish meal with corn as a carbohydrate (1863 m 3 /tonne), and the most energy intensive diet was high fish meal with corn as a carbohydrate (11.73 GJ/tonne). The results herein suggest that intensifying shrimp aquaculture could save resources based on per tonne of production basis. Graphical abstract: Image 1 Highlights: Intensive shrimp farms save land compared to extensive shrimp farms. Water exchange is the driving factor with regards to water use at shrimp farms. Energy use increases, but plateaus with intensification. There are tradeoffs with different feed ingredients and production systems.